Déploiements artistiques : objet-livre et écoféminisme - Émeline Chauvet (Itinéraires)
Based on a corpus emanating from French artists, consisting of the book Le guide pratique du féminisme divinatoire and the documentary accompanying its 2011 version, Sorcières, mes sœurs by French artist Camille Ducellier, as well as the “precious works” of the Gang of Witches collective, the objective of this research will be to shed light on the way in which French ecofeminist thought unfolds in particular forms that are as many artistic book objects. While pointing out the intrinsic particularities of each work, from Ducellier's humour to the aesthetic perfection of the artistic catalogues of Gang of Witches, we will develop the orientations and common motives of these examples of French-style artistic ecofeminism.